2023
DOI: 10.1021/acs.analchem.3c01897
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chemical Screening of Microplastics and Nanoplastics by Thermal Desorption and Pyrolysis Mass Spectrometry with Unsupervised Fuzzy Clustering

Thomas P. Forbes,
John M. Pettibone,
Eric Windsor
et al.

Abstract: The transport and chemical identification of microplastics and nanoplastics (MNPs) are critical to the concerns over plastic accumulation in the environment. Chemically and physically transient MNP species present unique challenges for isolation and analysis due to many factors such as their size, color, surface properties, morphology, and potential for chemical change. These factors contribute to the eventual environmental and toxicological impact of MNPs. As analytical methods and instrumentation continue to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Direct mass spectrometry methods were also reported for MPs and NPs. Forbes et al reported a new direct analysis in real time (DART)-MS method coupled to an IR thermal desorber . This direct method did not require chromatography and was very rapid compared to the “gold-standard” pyrolysis-GC-MS method.…”
Section: Microplasticsmentioning
confidence: 99%
“…Direct mass spectrometry methods were also reported for MPs and NPs. Forbes et al reported a new direct analysis in real time (DART)-MS method coupled to an IR thermal desorber . This direct method did not require chromatography and was very rapid compared to the “gold-standard” pyrolysis-GC-MS method.…”
Section: Microplasticsmentioning
confidence: 99%